Novel oxytocin receptor antagonists for tocolysis: a systematic review and meta-analysis of the available data on the efficacy, safety, and tolerability of retosiban. (2nd September 2021) - Marchand, Greg; Blumrick, Richard; Ruuska, Alexandra D.; Ware, Kelly; Masoud, Ahmed Taher; King, Alexa; Ruther, Stacy; Brazil, Giovanna; Cieminski, Kaitlynne; Calteux, Nicolas; Ulibarri, Hollie; Sainz, Katelyn
Abstract: Objective: To assess the efficacy, safety, and tolerability of retosiban—a novel tocolytic unavailable in the US—in the management of preterm labor. Methods: We searched ClinicalTrials.Gov, MEDLINE, PubMed, SCOPUS, Web of Science, and the Cochrane Library for relevant clinical trials using the terms "retosiban" and "preterm labor" through 09/2020. We included all published randomized clinical trials (three) that compared retosiban to placebo for preterm labor, excluding conferences, books, reviews, posters, case reports, and animal studies. We analyzed homogeneous data under the fixed-effects model and heterogeneous data under the random-effects model. Results: We included all randomized clinical trials addressing this topic, which ultimately resulted in three trials with a total of 116 patients. There were no significant differences between retosiban and placebo in births at term (RR = 0.41, p = .02), births ≤7 days from the first study treatment (RR = 0.59, p = .23), or administration of rescue tocolytic (RR = 0.36, p = .07); the maternal adverse events of headache, anemia, constipation, or urinary tract infection ( p > .05); or neonatal outcomes of Apgar score at 1 min ( p = .88) or 5 min ( p = .69), weight ( p = .23), head circumference ( p = .55), malnutrition ( p = .27), hyperbilirubinemia (RR = 0.56, p = .21), jaundice (RR = 1.21, p = .84), respiratory distress (RR = 0.53, p = .49), or tachypnea (RR = 0.40, p = .42). Conclusion: With the limited high quality evidence available, retosiban demonstrates no clear benefit over placebo in the management of preterm labor. Nevertheless, its favorable safety profile, oral bioavailability, and novel mechanism of action and the limited number of studies available for review warrant further analysis.